The effect of receiving a diagnosis of dementia on social engagement among older adults. (December 2021) - Amano, Takashi; Jia, Yuane; Reynolds, Addam; Scher, Clara
Abstract: Background: Early diagnosis has been recognized as a key strategy to improve outcomes of Alzheimer's disease and related dementias. However, due to the stigmatization of these disorders, practitioners need to recognize and weigh the relative dis/advantages of receiving a diagnosis on patients' well‐being. Despite this need, the social consequences of receiving a diagnosis have not been well investigated. This study closes this gap by examining if receiving a diagnosis of dementia influences social engagement among older adults. Method: Data from Health and Retirement Study (HRS; 2012, 2014, and 2016), a nationally representative sample of people who are 51 years or older in the United States, were utilized. Social engagement is measured with a previously developed scale using five social activities (e.g. volunteering, attending educational courses, attending clubs). Dementia diagnosis was measured by asking respondents or their proxy whether they had ever been told by a doctor that they had dementia or Alzheimer's disease. Propensity score weighted Poisson regression was utilized with adjustment (doubly robust) to control for potential systematic selection of receiving a diagnosis of dementia such as functional, sociodemographic, and health service‐related factors. Result: Receiving a new diagnosis of dementia statistically significantly reduced the score of social engagement two years later ( b = ‐0.360, p = 0.031, 95% CI = [‐0.686, ‐0.033]). The effect of receiving a diagnosis was more salient in the model which adjusted for socioeconomic factors ( b = ‐0.649, p < 0.001, 95% CI = [‐0.866, ‐0.432]). An interaction between receiving a diagnosis of dementia and household income was significant, indicating that the effect of receiving a diagnosis varies depending on the household income of the recipient. Conclusion: Results suggest that receiving a new diagnosis of dementia may discourage people from maintaining their level of social engagement, regardless of their abilities to participate in activities. The significant interaction term implies that people with lower household income may be more susceptible to the negative impact of receiving a diagnosis of dementia on staying socially engaged. Practical attention should be paid especially to social disengagement among people with disadvantaged socioeconomic status after receiving a diagnosis of dementia.